Narrative Self-Healing in Ian McEwan’s The Atonement - Mateus Rudi Supsiadji; Tegar Febrian Putra (Anaphora : Journal of Language, Literary, and Cultural Studies, 2022)
This study explores Briony's narrative self-healing to promote her healing. The purpose of this study is to clarify the portrayal of narrative self-healing in Atonement. The author adopts a psychology-analytical approach, focusing on the Four Stages of Psychotherapy in particular (Jung, 1966: 53-75). Confession, explanation, education, and transformation are the four stages of Jung's four-stage psychotherapy. The author also uses qualitative descriptive analysis to examine the various forms of Briony's narrative self-healing in Atonement. Through this study, the author learns how Briony reveals her narrative self-healing in Atonement, including her confession of her guilt that she accused Robbie of doing bad things, her explanation of her guilts to Robbie, her explanation of her effort to make some apologies for her guilty and the transformation of her guilt feeling.